Roman Religion and Cults in Epidaurum (Archaeologia Adriatica, 2012)
The Roman colony of Epidaurum (modern-day Cavtat) has been poorly excavated, which represents the main problem in a study of any aspect of Roman life in the area of present-day Dubrovnik. however, thanks to epigraphic holdings, material remains, certain traditions and other indicators, it is possible to say something about Roman religion and cults in Epidaurum in the period of Roman rule over the Croatian coastal region. So far, we have succeeded in identifying the following worshipped deities and cults: Jupiter, Minerva, Diana, Aesculapius, the imperial cult and Mithra. Jupiter, Diana and an unknown deity have been confirmed by an inscription, while the worship of Minerva has been confirmed only in private in the form of a bronze statue. The cult of Aesculapius is suggested by tradition and analogies with Narona, though three decorative pieces with his figure on them cannot be considered sufficient proof of public worship of the cult. The imperial cult has also been confirmed by two inscriptions, and also indirectly by the testimony of the Dolabela inscription. Mithra is the most well-known and confirmed deity in the Cavtat area. however, no inscriptions have been found bearing his name. As new archaeological excavations are still to follow, and the ones that have commenced have not been completed yet, the list of worshipped deities and cults in the area of Cavtat and its surroundings will certainly be longer, and our insights much better supported. There is a clear distribution of the abovementioned cults and deities in the wider area of the former colony of Epidaurum, which serves as a good indicator of the Romanisation of the Dubrovnik region.
Keywords: Epidaurum; Cavtat; Jupiter; Minerva; Aesculapius; imperial cult; Mithra